Le protesi nelle fratture del collo femorale - Pantalone, A.; Polidoro, F.; Rea, R.; Salini, V. (Lo Scalpello - Journal, 2019)
HIP PROSTHESIS FOR FEMORAL NECK FRACTURESIntracapsular fractures of the proximal femur account for a major share of fractures in the elderly and result from lowenergy trauma; in these cases hip replacement arthroplasty is a viable treatment option. A timely and appropriatetreatment of hip or proximal femur fracture lead to reduction in the risk of complications associated with prolongedbed rest in older persons. In this regard, the use of different prosthetic hip joints should be considered to achieve thebest risk-benefit and cost-effective ratio.